2006
DOI: 10.14742/ajet.1307
|View full text |Cite
|
Sign up to set email alerts
|

Using asynchronous online discussions in primary school project work

Abstract: <span>Using asynchronous online discussions for interschool collaborative project work represents one of the innovative practices in the Singapore classroom. With anytime, anywhere access to interactions among the students and teachers, the asynchronous nature of these interactions leads to new paradigms for teaching and learning, with both unique problems of coordination and unique opportunities to support active participation and collaborative learning. A research study was conducted to investigate how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
2
4
0
1
Order By: Relevance
“…A similar trend in primary and secondary school students' interaction was observed both in this study and the previous study (Jamaludin & Quek, 2006), that is these students' participation notes resided mainly at phase I and to a lesser extent in phases II to V. The explanation for the large percentage of phase I notes could be that coconstruction of knowledge may not always be an observable phenomenon in the online learning environment (Kosiak 2004). Basically, IAM provided the type of discourse that was most frequently used in the online discussions and determined the progression of the postings throughout the different phases of the model.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A similar trend in primary and secondary school students' interaction was observed both in this study and the previous study (Jamaludin & Quek, 2006), that is these students' participation notes resided mainly at phase I and to a lesser extent in phases II to V. The explanation for the large percentage of phase I notes could be that coconstruction of knowledge may not always be an observable phenomenon in the online learning environment (Kosiak 2004). Basically, IAM provided the type of discourse that was most frequently used in the online discussions and determined the progression of the postings throughout the different phases of the model.…”
Section: Discussionsupporting
confidence: 86%
“…Only a small percentage of contributions (3.8%) could be categorised as higher order cognition (phases III, IV and V) and awareness of knowledge construction. Interestingly, a similar trend was also found in the earlier case study conducted in five primary schools' asynchronous online project-based classrooms (Jamaludin & Quek, 2006) where students' notes mainly resided in phase I but not phase III and beyond. The findings seemed to suggest there is a need to further investigate (a) why students did not move beyond phase III of knowledge construction, (b) what teachers could do to help students achieve higher order thinking and (c) how students could interact not just socially but more cognitively, leading to deeper understanding of learning with one another.…”
Section: Phii/c]supporting
confidence: 81%
See 1 more Smart Citation
“…Many previous studies have found that limited student contribution in online discussion forums to be a persistent and widespread problem (Burt et al 1994;Cheong and Cheung 2008;Hew 2004, 2006;De Wever et al 2006;Guzdial 1997;Hew and Cheung 2003a;Jamaludin and Quek 2006;Kanuka and Anderson 1998;Khine et al 2003;Kucuk et al 2010;Lazonder et al 2003;Lee et al 2011;Maor 2010;McLoughlin and Luca 2000;Wan and Johnson 1994;Yukselturk 2010).…”
Section: Limited Student Contributionmentioning
confidence: 99%
“…The mediation of technology in this context involves technology acting as intermediary agent in effecting communication among learners in an online environment. In such an environment, teachers play major roles in designing the educational experience, facilitating the learning and providing direct instruction (Anderson, Rourke, Garrison & Archer, 2001;Jamaludin & Quek, 2006).…”
Section: Introductionmentioning
confidence: 99%